Experimental Study on Lean Coal and Gas Combined Combustion Boiler - YI Zheng ming; HU Xu man; ZHOU Zheng; TAO Qian; XIAO Hui; JIANG Zhi wei (Journal of Harbin University of Science and Technology)
In order to study the effects of blending ratio on exhaust temperature, superheated steam temperature, carbon content in fly ash and slag, and boiler thermal efficiency, and put forward the corresponding operation optimization method, mixed combustion experiments of COG (coke oven gas) with coal, BFG (blast furnace gas) with COG, and coal, BFG with COG were performed in a 75t/h combined combustion boiler, respectively The results show that the boiler thermal efficiency can reach 827% under the condition of mixed combustion of COG and coal, but the operating mode is not economical for the gas balance of plant When burning BFG and COG in the boiler, the boiler thermal efficiency can reach 852% but low loading operation After the mode of 35% BFG heat value, 35% COG heat value and 30% lean coal heat value is applied in the boiler, the exhaust temperature, carbon content in fly ash and slag decreases by 45℃, 106% and 109%, respectively The boiler thermal efficiency is 7721% Moreover, the fuel consumption reduces by 2261kg/h and the coal saving ratio is 33%